If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4n + -3n + -7 = 54 Reorder the terms: -7 + 4n + -3n = 54 Combine like terms: 4n + -3n = 1n -7 + 1n = 54 Solving -7 + 1n = 54 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '7' to each side of the equation. -7 + 7 + 1n = 54 + 7 Combine like terms: -7 + 7 = 0 0 + 1n = 54 + 7 1n = 54 + 7 Combine like terms: 54 + 7 = 61 1n = 61 Divide each side by '1'. n = 61 Simplifying n = 61
| 0.4x-0.5(2x+7)=0.7(x+3) | | 2+35324= | | -66=-11g+33 | | -4a+24+6a=3a-7a | | -2(12y)= | | 5m(4m^3-3m^2+2)= | | 2000+25x=0 | | 14a=2a+60 | | 6+11x=-40 | | 5-x=5x+34 | | -9+n=17 | | -26+x=x+23 | | 10-8x-7-2x=5 | | -4(z+2)+2z= | | -9*n=17 | | 0.7x-0.1(15-3x)=0.5(x-6) | | 3+4(2x-14)=-27 | | 1.5x=1.25x+8 | | y=400(13-x^2)(7x-8) | | 2x*2x+3y+3y+3y-x-x-x-x-y-y-y= | | x^2-4xy-21y^2= | | 8+7(7x-4)= | | 5-(x-7)+4x=7(x-1) | | 14-(3+3x)=x-9 | | 5y-7=0.6 | | -11x^3=704 | | -6(n-4)=40-4n | | 14(y-3)=10(5+y) | | 3(3x+4)-3=66 | | 3(3+4x)-3=66 | | x^2+37x+36= | | 7x-6x=70 |